Masculinity and spirituality in Victorian culture / edited by Andrew Bradstock ... [et al.]. - Bradstock, Andrew (Macmillan, 2000)
In its specially commissioned 14 chapters, this book discusses a range of issues around the theme of male spirituality in the 19th century, drawing from history, cultural studies, art history and literary criticism.